DEVELOPING STUDENTS' CRITICAL THINKING SKILLS THROUGH CONSTRUCTIVIST LEARNING IN FIQIH STUDY - Nurul Muti’ah; Andi Prastowo (STAI Sebelas April Sumedang, 2024)
The ability to think critically is a fundamental ability that everyone needs to have in facing current challenges. So that the low critical thinking ability of students is currently an important problem in education. at Madrasah Diniyah Nurul Ummah Putri itself there is still a lack of critical thinking skills, for example when students are given hot questions, story questions or true and false questions there are still many who are confused and do not understand. This study aims to find out how the concept of constructivism learning in training students' critical thinking skills in fiqh subjects at madrasah diniyah nurul ummah Putri. This study uses a descriptive qualitative approach, collecting data using three methods, namely, observation, interviews, and documentation. The results of the research show that there are still students who cannot think critically, therefore the teacher must be able to use the right learning model, which can refer to students' critical thinking abilities, and the learning model used must be adapted to constructivism learning theory, which students must build knowledge in his own mind. Student- centered learning and the teacher only acts as a facilitator